2012
DOI: 10.2478/v10058-012-0038-5
|View full text |Cite
|
Sign up to set email alerts
|

Polar cartilages and formation of Crista sellaris in grass snake, natrix natrix (Ophidia, Colubridae), chondrocranium at the early stages of embryogenesis

Abstract: Polar Cartilages and Formation of Crista Sellaris in Grass Snake, Natrix natrix (Ophidia, Colubridae), Chondrocranium at the Early Stages of Embryogenesis. Sheverdyukova H. V.- The initial developmental stages of grass snake’s, Natrix natrix Linnaeus, 1758 chondrocranium are described. Three paired structures form the floor of N. natrix’s neurocranium: cranial trabeculae, polar cartilages, and parachordals. The primordiums of polar cartilages and their independent centers of chondrification are identified at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…In contrast to other authors, Parker () observed the formation of the transverse bar (crista sellaris) in N. natrix as a result of the fusion of processes extending from the confluence of the trabeculae and parachordals (which is analogous to the description of de Beer in L. agilis ). According to our data (Sheverdyukova, ), the crista sellaris in N. natrix is formed in a way similar to that described by Parker (). The only difference is that the merging processes would derive not from the place where the parachordials and cranial trabeculae confluence, but from the polar cartilages.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In contrast to other authors, Parker () observed the formation of the transverse bar (crista sellaris) in N. natrix as a result of the fusion of processes extending from the confluence of the trabeculae and parachordals (which is analogous to the description of de Beer in L. agilis ). According to our data (Sheverdyukova, ), the crista sellaris in N. natrix is formed in a way similar to that described by Parker (). The only difference is that the merging processes would derive not from the place where the parachordials and cranial trabeculae confluence, but from the polar cartilages.…”
Section: Discussionsupporting
confidence: 84%
“…Sheverdyukova () described the formation of the transverse bar (crista sellaris) at successive developmental stages in N. natrix (Linnaeus, 1758) (Colubridae) embryogenesis in detail. Its formation is similar to that described by Parker () in N. natrix and de Beer () in L. agilis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reptiles, some descriptions exist on phylogenetic “key species” such as the tuatara Sphenodon punctatus (Figure f,g) (Howes & Swinnerton, ; Schauinsland, ; Werner, ) or easily available species such as Grass snake Natrix natrix (Bäckström, ; Chekanovskaya, ; Kovtun & Sheverdyukova, ; Parker, ; Sheverdyukova, ,b) and the Sand lizard Lacerta agilis (de Beer, ; Gaupp, ; Kovtun & Yaryhin, ; Yaryhin, , ; Yaryhin & Klembara, ; Yaryhin & Werneburg, , ). A detailed observation on the variation of basitrabecular process chondrification, for example, resulted in the finding of a unique pattern.…”
Section: Intra‐ and Interspecific Variabilitymentioning
confidence: 99%